Neuroprotective Effects of Lacosamide in Experimental Peripheral Nerve Injury in Rats : A Prospective Randomized and Placebo-Controlled Trial - Demiroz, Serdar (J Korean Neurosurg Soc, 2020)
OBJECTIVE: To evaluate the neuroprotective effects of lacosamide after experimental peripheral nerve injury in rats. METHODS: A total of 28 male wistar albino rats weighing 300–350 g were divided into four groups. In group I, the sciatic nerve exposed and the surgical wound was closed without injury; in group II, peripheral nerve injuries (PNI) was performed after dissection of the nerve; in group III, PNI was performed after dissection and lacosamide was administered, and in group IV, PNI was performed after dissection and physiological saline solution was administered. At 7 days after the injury all animals were sacrificed after walking track analysis. A 5 mL blood sample was drawn for biochemical analysis, and sciatic nerve tissues were removed for histopathological examination. RESULTS: There is low tissue damage in lacosamide treated group and antioxidant anzymes and malondialdehyde levels were higher than non-treated and placebo treated group. However there was no improvement on clinical assessment. CONCLUSION: The biochemical and histological analyses revealed that lacosamide has neuroprotective effect in PNI in rats. This neuroprotective capacity depends on its scavenger role for free oxygen radicals by increasing antioxidant enzyme activity.